Development of Loop-Mediated Isothermal Amplification Assay Targeting lytA and psaA Genes for Rapid and Visual Diagnosis of Streptococcus pneumoniae Pneumonia in Children - Du, Shuheng; Yan, Chao; Du, Bing; Zhao, Hanqing; Xue, Guanhua; Zheng, Ping; Feng, Yanling; Cui, Jinghua; Gan, Lin; Feng, Junxia; Fan, Zheng; Xu, Ziying; et al. (Frontiers in Microbiology, 2022)
Streptococcus pneumoniae (S. pneumoniae) is a common major human pathogen associated with community acquired pneumoniae, septicemia, meningitis, and otitis media. It is difficult to isolate and identify S. pneumoniae form clinical samples. To evaluate a novel, rapid, sensitive, and specific loop-mediated isothermal amplification (LAMP) assay to detect S. pneumoniae pneumonia in children, we designed specific LAMP primers targeting lytA and psaA genes. We optimized the reaction time and reaction system, and evaluated its sensitivity and specificity of detection using real-time turbidity monitoring and visual observation. We also analyzed the molecular characteristics of the isolates obtained from the positive samples. The primer sets LytA-1 and PsaA-2 amplified the genes in the shortest times, and 63 ℃ was confirmed as the optimum reaction temperature. The detection sensitivity of each reaction was 10 and 100 copies/μL with primer sets LytA-1 and PsaA-2, respectively. This LAMP assay showed no cross-reactivity with other 27 pathogens. To describe the availability of this method, we collected 748 clinical samples from children with pneumonia. Among them, 135 were confirmed to be S. pneumoniae positive by LAMP. The sensitivity was 100% (95% CI 96.4%–100%), specificity 99.0% (95% CI 97.8%–99.6%). Including them, 50 were co-infected with Mycoplasma pneumoniae. This LAMP assay detected S. pneumoniae in 1 hour and the results can be identified with visual naked eyes. Thus, it will be a powerful tool for S. pneumoniae early diagnosis and effective antibiotic therapy.